THE EFFECT OF INTERPERSONAL CONFLICT, WORKLOAD AND COMMUNICATION ON EMPLOYEES WORK STRESS AT PT.SATYA KISMA BUSINESS IN LABUHANBATU SELATAN DISTRICT - Yanita; Fiti Susanti Nasution (CV. Radja Publika, 2022)
This study aims to determine how the influence of interpersonal conflict, workload, and communication on work stress. This research was conducted at PT. Satya Kisma Usaha in South Labuhanbatu Regency. The data used in this study is primary data obtained by distributing questionnaires to 91 working employees, then the data analysis technique used is multiple linear regression analysis consisting of data instrument testing, classical assumption testing and hypothesis testing. The results of the study concluded that partially interpersonal conflict and workload had a positive and significant effect on work stress on employees, while communication partially had a negative and significant effect on work stress on employees.